Buddhist funeral cultures of Southeast Asia and China - Williams, Paul, 1950-; Ladwig, Patrice (Cambridge University Press, 2012)
"The centrality of death rituals has in anthropologically informed studies of Buddhism been little documented. The current volume brings together a range of perspectives on Buddhist death rituals including ethnographic, textual, historical and theoretically informed accounts, and presents the diversity of the Buddhist funeral cultures of mainland Southeast Asia and China. It arises out of the University of Bristol's Centre for Buddhist Studies research project Buddhist Death Rituals in Southeast Asia and China, funded by the United Kingdom's Arts and Humanities Research Council. This project involved extensive new research in Thailand, Laos and China. Other items from that project included several public exhibitions, extensive stills photographs, and several video films. The project-team produced two 30 minutes films on the ghost festival in Laos and China, one on urban funerals in Chiang Mai (Thailand) and several shorter clips dealing with funeral cultures in Laos, Thailand and China. Most of this material (and an extensive bibliography on the topic) is available free of charge from the project website located at the webpage of the Department of Theology and Religious Studies (Centre for Buddhist Studies) at the University of Bristol"-- Provided by publisher.
Keywords: Buddhist funeral rites and ceremonies -- Southeast Asia.; Buddhist funeral rites and ceremonies -- China.; Funérailles -- Rites et cérémonies bouddhiques -- Asie du Sud-Est.; Funérailles -- Rites et cérémonies bouddhiques -- Chine.; RELIGION -- Buddhism -- General (see also PHILOSOPHY -- Buddhist); Buddhist funeral rites and ceremonies; China; Southeast Asia